Posttranslational modifications in the CP43 subunit of photosystem II - Anderson, Lorraine B.; Maderia, Melissa; Ouellette, Anthony J. A.; Putnam-Evans, Cindy; Higgins, LeeAnn; Krick, Thomas; MacCoss, MIchael J.; Lim, Hango; Yates, John R. III; Barry, Bridgette A. (East Carolina University, 2002)
Photosystem II (PSII) catalyzes the light-driven oxidation of water and the reduction of plastoquinone; the oxidation of water occurs at a cluster of four manganese. The PSII CP43 subunit functions in light harvesting, and mutations in the fifth luminal loop (E) of CP43 have established its importance in PSII structure and or assembly [Kuhn, M. G. & Vermaas, V. F. J. (1993) Plant Mol. Biol. 23, 123–133]. The sequence A350PWLEPLR357 in luminal loop E is conserved in CP43 genes from 50 organisms. To map important posttranslational modifications in this sequence, tandem mass spectrometry (MS MS) was used. These data show that the indole side chain of Trp-352 is posttranslationally modified to give mass shifts of +4, +16, and +18 daltons. The masses of the modifications suggest that the tryptophan is modified to kynurenine (+4), a keto- amino- hydroxy- (+16) derivative, and a dihydro-hydroxy- (+18) derivative of the indole side chain. Peptide synthesis and MS MS confirmed the kynurenine assignment. The +16 and +18 tryptophan modifications may be intermediates formed during the oxidative cleavage of the indole ring to give kynurenine. The sitedirected mutations, W352C, W352L, and W352A, exhibit an increased rate of photoinhibition relative to wild type. We hypothesize that Trp-352 oxidative modifications are a byproduct of PSII water-splitting or electron transfer reactions and that these modifications target PSII for turnover. As a step toward understanding the tertiary structure of this CP43 peptide, structural modeling was performed by using molecular dynamics. Originally published Proceedings of the National Academy of Sciences, Vol. 99, No. 23, Nov 2002
Keywords: Mass spectrometry; Collision-induced dissociation; Tryptophan; Kynurenine; Photoinhibition